Peningkatan Hasil Belajar IPAS pada Materi Bagian-Bagian Tumbuhan Dengan Model Pembelajaran Role Playing Pada Siswa Kelas IV di SD Negeri 12 Lubuk Besar - anggun123 pratiwi; M Iqbal Arrosyad; Gatot Afrianto (CENDEKIAWAN, 2025)
The low student learning outcomes are due to the outdated teaching methods still employed by teachers, leading to a lack of interest in IPAS learning. A change in learning implementation using role-playing models is necessary. The research question is whether the role-playing method can improve the learning outcomes of fourth-grade students at SD Negeri 12 Lubuk Besar. The purpose of this study is to determine the implementation of role-playing models in improving student learning outcomes. This study uses Classroom Action Research. Data analysis is conducted using quantitative descriptive methods. The results show that the role-playing method can improve student learning outcomes, as evidenced by the increase in mastery scores and average scores. In the first cycle, 10 students achieved mastery, and in the second cycle, it increased to 19 students. The average score also increased from 62.4 in the first cycle to 77 in the second cycle. Therefore, it can be concluded that implementing the role-playing method can improve the learning outcomes of fourth-grade students at SD Negeri 12 Lubuk Besar. The researcher hopes that future studies can further enhance IPAS learning and optimize learning time in applying the role-playing model.